Unlocking Science Potential: Developing a New Attitude Scale SS-SAS for Young Learners - Seema Lenin Koshy; Shruti Tiwari (International Journal of Behavioral Sciences, 2025)
The aim of this examination is to develop an attitude scale for measurement of scientific attitude of upper primary students. The development was carried out by researchers with the help of 20 subject area experts, and 240 students of approved schools of state of Rajasthan State/central boards BE/CBSE board studying in classes 6–8. The study consists of five parts, namely literature review, components of scientific attitude to be measured, development of scale, expert opinions, administration of scale and computation of reliability and validity. For identifying the components of scientific attitude an extensive review of related was carried out and five components were identified. An initial draft of scientific attitude scale (SAS) comprising of 65 items was forwarded to 20 experts for Face and Content validity. Subsequently Content Validity Ratios were calculated and Final SAS tool comprising of 62 items was formulated. This was then administered to 20 percent (48) of total sample (240 students) students. Reliability of the test was calculated for SAS using Split Half (Odd-Even) Correlation and split half reliability to the correlation coefficient yielded a reliability coefficient of .882. Tool had five aspects on scientific attitude for which separately Pearson‟s correlation has been found out to be 0.799. Final outcome of the study. The scale with 62 statements was ready to be used.
Keywords: SS-SAS; Scientific attitude; content validity ratio; scientific attitude scale; statistical analysis